2011
DOI: 10.4315/0362-028x.jfp-10-434
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extracts of Tulbaghia violacea Inhibit Germination of Aspergillus flavus and Aspergillus parasiticus Conidia

Abstract: Aspergillus flavus and Aspergillus parasiticus are important plant pathogens and causal agents of pre- and postharvest rots of corn, peanuts, and tree nuts. These fungal pathogens cause significant crop losses and produce aflatoxins, which contaminate many food products and contribute to liver cancer worldwide. Aqueous preparations of Tulbaghia violacea (wild garlic) were antifungal and at 10 mg/ml resulted in sustained growth inhibition of greater than 50% for both A. flavus and A. parasiticus. Light microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Saccharomyces cerevisiae EBF101 and S. cerevisiae 117 exhibited the maximal levels of growth inhibition against A. flavus Z103 with clear zones up to 4Á2 and 3Á5 cm, respectively. Recently, several authors recorded the antagonistic effect of S. cerevisiae against A. flavus (Joannis-Cassan et al 2011;Prado et al 2011;Somai and Belewa 2011). The antagonistic ability of S. cerevisiae might be related to the competition for nutrients and space, direct contact and production of hydrolytic enzymes (Lima et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Saccharomyces cerevisiae EBF101 and S. cerevisiae 117 exhibited the maximal levels of growth inhibition against A. flavus Z103 with clear zones up to 4Á2 and 3Á5 cm, respectively. Recently, several authors recorded the antagonistic effect of S. cerevisiae against A. flavus (Joannis-Cassan et al 2011;Prado et al 2011;Somai and Belewa 2011). The antagonistic ability of S. cerevisiae might be related to the competition for nutrients and space, direct contact and production of hydrolytic enzymes (Lima et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study (Somai and Belewa ) found that the cell walls of A. flavus and A. parasiticus , two closely related fungi, had undergone morphological changes when exposed to subinhibitory doses of T. violacea plant extract. This appears to be a normal reaction in fungi when exposed to plant extracts and has been reported previously (Rasooli et al .…”
Section: Discussionmentioning
confidence: 99%
“…). Electron micrographs of spores exposed to the plant extract indicated that the extract induced remodelling of the spore cell wall (Somai and Belewa ). This study expands on the above research by focusing on the effects of the plant extract on A. flavus cell wall specifically by investigating changes in the β ‐(1,3) glucan and chitin production and on the β ‐(1,3) glucan and chitin synthases responsible for their biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are considerable discrepancies in the antimicrobial assay results reported. Whereas some authors have found the plant to be completely devoid of antimicrobial activity (McGaw et al, 2000;Bamuamba et al, 2008;Nyila et al, 2012), others have observed significant antimicrobial properties in various Tulbaghia extracts (Motsei et al, 2003;Lindsey and Van Staden, 2004;Thamburan et al, 2006;Nteso and Pretorius, 2006a,b;Buwa and Afolayan, 2009;Belewa et al, 2011;Somai and Belewa, 2011;Jäger and Stafford, 2012;Soyingbe et al, 2013).…”
Section: Introductionmentioning
confidence: 95%